2021
DOI: 10.34312/jgeosrev.v3i2.10443
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Correlation Map Between Estimated ENSO And IOD From ERA5 And Hotspot In Indonesia

Abstract: El Nino-Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) can reduce the amount of rainfall in Indonesia. The previous study found that ENSO and IOD derived from the OISST dataset have an association with hotspots in Indonesia, especially in southern Sumatra dan Kalimantan. But the correlation results are still too small, and the correlation strength between regions has not been analyzed. Therefore, this study quantifies the association of the estimated ENSO and IOD derived from the ERA5 dataset on hot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For estimating fire risk using Canadian Forest FWI, we used the European Centre for Medium range Weather Forecasts Reanalysis (ERA5) daily reanalysis data (Hersbach et al, 2020) including rainfall, air temperature at 2 m, relative humidity at 1000 hPa as well as zonal wind and meridional wind at 10 m, thanks to the availability of these variables at a high resolution of 0.25° online. We also used the ERA5 data for estimating zonal winds over equatorial Western Pacific, as it has a good track record of capturing ENSO and its related teleconnections as in previous studies despite being a reanalysis product (Capotondi & Ricciardulli, 2021; Nikonovas et al, 2022; Nurdiati et al, 2021). For sea surface temperature over eastern North Pacific, we chose monthly HadISST2.0 as it is embedded with satellite measurements (Kennedy et al, 2013).…”
Section: Study Area and Datasetsmentioning
confidence: 99%
“…For estimating fire risk using Canadian Forest FWI, we used the European Centre for Medium range Weather Forecasts Reanalysis (ERA5) daily reanalysis data (Hersbach et al, 2020) including rainfall, air temperature at 2 m, relative humidity at 1000 hPa as well as zonal wind and meridional wind at 10 m, thanks to the availability of these variables at a high resolution of 0.25° online. We also used the ERA5 data for estimating zonal winds over equatorial Western Pacific, as it has a good track record of capturing ENSO and its related teleconnections as in previous studies despite being a reanalysis product (Capotondi & Ricciardulli, 2021; Nikonovas et al, 2022; Nurdiati et al, 2021). For sea surface temperature over eastern North Pacific, we chose monthly HadISST2.0 as it is embedded with satellite measurements (Kennedy et al, 2013).…”
Section: Study Area and Datasetsmentioning
confidence: 99%
“…It has been previously researched that fires in Indonesia are strongly influenced by local climatic conditions (such as precipitation and dry spells) and regional climatic conditions such as the Indian Ocean Dipole (IOD) and El Nino-Southern Oscillation (ENSO) [34], [35]. Based on the systematic literature review description, several research opportunities related to the copula model in wildfires analysis in Indonesia can be proposed with a research roadmap, as shown in Figure 3.…”
Section: Development Opportunities Of the Copula Model In Wildfires In Indonesiamentioning
confidence: 99%
“…Previous research has found that forest fires in Kalimantan are more sensitive to ENSO than IOD. Meanwhile, the effect of IOD on forest fires was more pronounced in the southern part of Sumatra because it is located near the Indian Ocean (Nurdiati et al, 2021). Moreover, although it has been mentioned that the lack of precipitation can be a triggering factor for forest fires, the total precipitation is insufficient to characterize forest fires in Indonesia.…”
Section: Introductionmentioning
confidence: 99%